Determinants Of Organizational Commitment Among Hospital Employees: The Mediating Role Of Work Engagement - Aulia, Sweet Nabila Imsaki; Anitra, Vera; Fauziah, Fenty (JURNAL MANAJEMEN DAN BISNIS, 2025)
Purpose – This study examines the influence of psychological capital and work environment on organizational commitment, with work engagement as a mediating variable among hospital employees. The research seeks to explain how both internal psychological resources and external workplace conditions contribute to fostering commitment in the healthcare sector. Novelty – Unlike previous studies that consistently report work engagement as a universal mediator, this study finds that engagement mediates only the relationship between the work environment and organizational commitment, not between psychological capital and commitment. This provides nuanced empirical evidence that challenges existing assumptions. Furthermore, by focusing on a private hospital in Indonesia, a setting that has received limited attention in organizational behavior research this study extends the geographical and contextual scope of current literature. Method – A quantitative approach with a cross-sectional survey design was employed. Data were collected from 201 hospital employees through systematic random sampling from a population of 404 staff. Partial Least Squares–Structural Equation Modeling (PLS-SEM) was used to test both direct and indirect relationships. Findings – The results show that psychological capital and work environment both significantly influence organizational commitment. Work engagement also has a positive effect on organizational commitment but mediates only the link between work environment and commitment. Limitations and Implications – The research is limited to a single private hospital, constraining the generalizability of findings. Nevertheless, it underscores the importance of strengthening employees’ psychological capital and improving the work environment to enhance organizational loyalty. Theoretically, the study refines the understanding of work engagement’s role as a conditional rather than universal mediator. Practically, the insights can guide hospital managers and policymakers in designing strategies that foster both engagement and commitment